Preparation and Optimization of Biodiesel Production from Mixed Feedstock Oil - Ferdous, Kaniz; Uddin, M. Rakib; Uddin, M. Rahim; Khan, Maksudur R.; Islam, M. A. (Science and Education Publishing, 2013)
In this paper, production of biodiesel from mixed feedstock oil (MFO) by three-step method and optimization of the process were studied by using regressive analysis. The random mixer of different oil was used for biodiesel preparation. The MFO contains 12 wt% free fatty acid (FFA) and its viscosity was 67.5 mm2/s. Because of higher FFA content transesterification method can’t be applied, so three-step method was conducted for biodiesel preparation. In the three-step method, the first step was saponification of the oil followed by acidification to produce FFA and finally esterification of FFA to produce biodiesel. In the saponification reaction, various reaction parameters such as oil to sodium hydroxide molar ratio and reaction time were optimized. Produced sodium soap was acidified with excess molar ratio of HCl to produced FFA. In the esterification reaction, produced FFA was reacted with methanol in presence of acid catalyst and the FFA content was reduced to 0.98wt%. A factorial design was studied based on viscosity for esterification reaction and developed to obtain the higher yield of biodiesel. Finally various properties of biodiesel such as FFA content, viscosity, specific gravity, cetane index, pour point etc. were measured and compared with biodiesel and petro-diesel standard.